Increases Activity and The Results of The Learner’s Study by Implementing Cooperative Learning Method Type TAI - Galuh Indah Zatadini; Erna Adhistya P; Noor Akhmad Setiawan (Pancaran Pendidikan, 2017)
Cooperative Learning is a model of learning taken by learners in the group, therefore, it will create many more learners to learn and collaborate. This research include in a class action model research aims to know the increase in activity and the results of the learner’s study on ICT subjects by using the method of Individualization Assisted Team (TAI). This research has three cycles with stages planning, implement1ation, observation and reflection which is done immediately when the learning activity. The outcomes learning research data is taken when the process of reflection after a posttest to all students when the study is completed. While the data retrieval process is done when the implementation of the activity when learners attend teaching and learning activities. From the results of research, the application of the cooperative learning model type TAI can increase the activity of the learners on a standard competency "Using Numeric Process Software to Produce the Information" and the basic competence “Makes the Document Processing Numbers with Variations of Text, Tables, Charts, Pictures and Diagrams". It can be seen from the increase in the percentage of the learner’s activity in the cycle I, II, and III. On the learners’ activity cycle I total percentage are 39.8% and still low. Later in the cycle II, their percentage was 78% and cycle III the total percentage was 55.7%. In addition to this type of cooperative learning, TAI can also enhance the learning outcome of students in all realm of affective, cognitive or psychomotor. This learning model can be one alternative that applied in the activity of learning but also must comply with the material or type of learning activities that will be done because of this learning model is only suitable for competence/problem can be resolved individually or groups.